The Sustainability of Semarang Kauman Village (When Conservation Meets Development) - Margareta Maria Sudarwani (University of Merdeka Malang, 2024)
Semarang has developed as a large coastal city with an important port due to its strategic and unique position. This strategic and unique position is shown by the hills at the top of the city such as Gajah Mungkur, Candi, Mrican, Mugas, Mount Sawo, Simongan and others as well as lowlands at the bottom of the city. One of the important historical ethnic villages to be appointed is Kampung Kauman, Semarang, which has a distinctive history related to the existence of the Great Mosque of Semarang. is an ancient village inhabited by local residents which began to be awakened during the reign of Ki Ageng Padang Aran. The Great Mosque of Semarang, although it is quite an old mosque, is the first mosque in the city of Semarang which was founded by Ki Ageng Padang Aran. The Great Mosque of Semarang is located in the old Semarang square complex which has the same pattern as Javanese city squares in general. There are many opinions regarding the term